2022
DOI: 10.1016/j.cub.2022.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory stimuli and moonwalker SEZ neurons can drive backward locomotion in Drosophila

Abstract: Highlights d MooSEZs elicit backward locomotion via MDN-dependent and MDN-independent pathways d MooSEZs are connected to MDNs and other descending neurons d MooSEZs and MDNs both respond to olfactory input d MooSEZs can trigger rotational backward locomotion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…In line with having a role in behavioral modulation, studies in crickets and locusts have demonstrated that changes in the firing rates of some DNs ( Böhm and Schildberger, 1992 ; Zorović and Hedwig, 2011 ) correlate with walking speed and turning ( Heinrich, 2002 ). Alternatively, DN subpopulations may represent parallel pathways that are recruited depending on sensory context ( Israel et al, 2022 ). For example, different groups of DNs may be differentially engaged during odor-evoked versus spontaneously-generated walking ( Heinrich, 2002 ; Kien, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with having a role in behavioral modulation, studies in crickets and locusts have demonstrated that changes in the firing rates of some DNs ( Böhm and Schildberger, 1992 ; Zorović and Hedwig, 2011 ) correlate with walking speed and turning ( Heinrich, 2002 ). Alternatively, DN subpopulations may represent parallel pathways that are recruited depending on sensory context ( Israel et al, 2022 ). For example, different groups of DNs may be differentially engaged during odor-evoked versus spontaneously-generated walking ( Heinrich, 2002 ; Kien, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…MDN controls backward walking when the fly encounters an impassable barrier [ 46 ]. A recent study found that olfactory stimuli induced backward locomotion was also regulated by this MDN neuron [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the utility of the flow chamber and gradient calibration for the study of small animal navigation, we investigated how larval Drosophila navigate butanone. Although butanone is not as commonly used as a stimulus with Drosophila as with C. elegans, butanone is known to be attractive to larval flies (Dubin et al, 1995(Dubin et al, , 1998 and has been variously reported to be attractive (Park et al, 2002) and aversive (Israel et al, 2022;Lerner et al, 2020) to adult flies. To investigate the larva's navigational strategy in a butanone gradient, we created a "cone" shaped butanone gradient over the agar substrate using the pre-equilibration protocol, as before, and we confirmed the presence and stability of the gradient by continuously measuring the spatial distribution of butanone upstream and downstream of the agar arena.…”
Section: Butanone Chemotaxis In Drosophila Larvaementioning
confidence: 99%